2020
DOI: 10.1016/j.cell.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Molecular Architecture of the Human γ-Tubulin Ring Complex

Abstract: Highlightsd High resolution cryo-EM structure of the native human gtubulin ring complex (g-TuRC)d Identification and structural models for g-tubulin, GCP2, GCP3, GCP4, GCP5, and GCP6d Identification of an actin-like protein in the g-TuRC lumen d Insights into the regulation of microtubule nucleation by the g-TuRC

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
246
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(272 citation statements)
references
References 82 publications
24
246
2
Order By: Relevance
“…We demonstrate that GCPs 4, 5, and 6 form a stable sub-complex that permits the association with γTuSCs into a functional γTuRC. Within the sub-complex, the stoichiometric ratio of these GCPs matches the values found in recently reported structures of native γTuRCs (Wieczorek et al, 2020; Consolati et al, 2019; Liu et al, 2019). We find that GCPs 2 and 3 are also present in our preparations of the sub-complex, but at a molar ratio equivalent to half-a-γTuSC.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We demonstrate that GCPs 4, 5, and 6 form a stable sub-complex that permits the association with γTuSCs into a functional γTuRC. Within the sub-complex, the stoichiometric ratio of these GCPs matches the values found in recently reported structures of native γTuRCs (Wieczorek et al, 2020; Consolati et al, 2019; Liu et al, 2019). We find that GCPs 2 and 3 are also present in our preparations of the sub-complex, but at a molar ratio equivalent to half-a-γTuSC.…”
Section: Discussionsupporting
confidence: 87%
“…Since Wieczorek et al (2020) and Liu et al (2019) suggested the existence of γTuSC-like structures, containing pairs of GCPs 4/5 or GCPs 4/6, we tested how the depletion of individual GCPs 4, 5, or 6 affected the composition of the GCP4/5/6 sub-complex, and whether the proposed γTuSC-like structures did indeed exist. We depleted each of these three GCPs individually by RNAi, which resulted in each case in the loss of γTuRCs and in the accumulation of γTuSCs, as seen in sucrose gradients (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations